Ефективність алергенспецифічної імунотерапії пилковими алергенами в дітей із позиції молекулярної алергології - Недельська, Світлана Миколаївна; Кузнєцова, Олена Дмитрівна; Недельская, С. Н.; Кузнецова, О. Д.; Nedelska, S. M.; Kuznietsova, O. D. (Донецк: Заславский, 2017)
Мета роботи — встановити можливі причини неефективності алергенспецифічної імунотерапії (АСІТ) пилковими алергенами (бур’янів) у дітей із сезонним алергічним ринітом і/або бронхіальною астмою на підставі вивчення гіперчутливості до алергенів, аналізу анамнестичних даних. Матеріали та методи. Проведено алерготестування 192 дітей. 52 пацієнтам проведене анамнестичне опитування з акцентом на перехресну алергію та супутню патологію верхніх дихальних шляхів, а також на ефективність АСІТ. Статистична обробка результатів проведена в програмі Statistica for Windows 6.0. Цель работы — установить возможные причины неэффективности аллергенспецифической иммунотерапии (АСИТ) пыльцевыми аллергенами у детей с сезонным аллергическим ринитом и/или бронхиальной астмой на основании изучения гиперчувствительности к аллергенам, анализа анамнестических данных. Материалы и методы. Проведено аллерготестирование 192 детей. 52 пациентам проведен анамнестических опрос с акцентом на перекрестную аллергию и сопутствующую патологию верхних дыхательных путей, а также эффективность АСИТ. Статистическая обработка результатов проведена в программе Statisticа for Windows 6.0. Background. Allergen-specific immunotherapy as elimination procedures is the only method of treatment and prevention of allergic disorders formation and exacerbation of clinical symptoms. One of the approaches to molecular diagnosis is choice of allergen for allergen-specific immunotherapy (ASIT). The purpose of our study was to identify possible reasons of failure of ASIT with pollen allergens (predominantly weeds) in children with seasonal allergic rhinitis (hay fever) and/or bronchial asthma based on studying hypersensitivity to the allergens, analysis of anamnestic data. Materials and methods. Allergy skin prick tests were conducted to 192 children (middle age 9.8 ± 2.7 years) with the seasonal symptoms of rhinitis and/or bronchial asthma according to standard methodology with pollen allergens of Immunolog Ltd (Vinnytsia). We evaluated positive results as 5 mm and higher diameter of papula/hyperemia. The anamnestic survey was carried out in 52 patients by means of the questionnaire that contained questions about cross allergy (pollen-food, oral allergy syndrome), concomitant pathology of upper respiratory tract and effectiveness of АSІТ, which is elaborated by us.
Эффективность аллергенспецифической иммунотерапии пыльцевыми аллергенами у детей с позиции молекулярной аллергологии
Effectiveness of allergen-specific immunotherapy with pollen allergens in children from the viewpoint of molecular allergology
Keywords: сезонний алергічний риніт; алергенспецифічна імунотерапія; діти; перехресна реактивність; сезонный аллергический ринит; алергенспецифическая иммунотерапия; перекрестная реактивность; seasonal allergic rhinitis; allergen-specific immunotherapy; children; cross reactivity